Pemberdayaan Masyarakat Membuat Dodol Pepaya di Desa Kemiri Kecamatan Mojosongo - Bimoseno Sepfrian; Rahmawati Setiyani; Ani Septia Sari; Dian Septi Purwani (Penerbit Goodwood, 2023)
Purpose: The achievement indicator in this community service program is the realization of independence in providing the ability of farmer households in processing papaya raw materials into papaya dodol as a characteristic of souvenirs from the Mojosongo Boyolali sub-district. The purpose of this service program is with this socialization and training to educate the public by utilizing the papaya fruit harvest, in this case the selected papaya is mojosongo so that it has added value, not only selling the fruit but also being processed into papaya dodol. Method: Methods of implementing activities include training and education socialization program for making papaya dodol for farmers' households. This community service program aims to transfer knowledge through community empowerment by socializing training and education on making papaya dodol. The activity began with the socialization of the benefits of papaya fruit training and the procedures for making papaya fruit dodol The next activity is education about making papaya fruit dodol. Result: The results of this activity the community was able to make dodol from the raw material of papaya mojosongo and benefited the community, especially in the Kemiri Village, Mojosongo Village, Boyolali Regency with the opening of business opportunities for making papaya dodol. Conclusion This community service activity is to transfer knowledge through community empowerment by socializing training and education on making papaya dodol in the Kemiri Village, Mojosongo Village, Boyolali Regency.